Key Oxidation Parameters that Influence Photo-Induced Properties and Applications of Anodic Titanium Oxides. Issue 2 (1st December 2015) - Piazza, Valerio; Mazare, Anca; Diamanti, Maria Vittoria; Pedeferri, MariaPia; Schmuki, Patrik
Abstract : In the present work we investigate compact anodic oxides formed on titanium by a broad range of anodizing parameters (electrolyte, applied voltage, substrate pre-treatment) and their influence on the performance of such oxides in photocurrent response and photocatalytic properties (photodegradation of AO7). In general, crystallinity and ion inclusion from the electrolyte are crucial. As-grown compact layers of partial crystallinity show increased efficiencies in both applications; interestingly, phosphate ions have a detrimental effect, whereas sulfate ions do not. After thermal annealing (crystallization) the photoresponse significantly increases: except for a crystallization of the anodic layer, annealing causes a rutile oxide layer growth at the oxide/metal interface - this is found to additionally affect the photoresponse. Results overall demonstrate that higher anodization voltage, exclusion of phosphates from the electrolyte, substrate pre-treatment and annealing are of major importance for achieving an enhanced photoresponse on compact anodic layers.